Comparison of Electrolyte Composition and Crystallization Patterns in Bird and Reptile Tears - Oriá, Arianne P.; Lacerda, Ariane de J.; Raposo, Ana Cláudia S.; Araújo, Nayone L. L. C.; Portela, Ricardo; Mendonça, Marcos A.; Masmali, Ali M. (Frontiers in Veterinary Science, 2020)
To compare tear electrolytes and tear crystallization patterns in birds and reptiles, tears were sampled by Schirmer tear test from 10 animals each of Ara ararauna, Amazona aestiva, Tyto alba, Rupornis magnirostris, Chelonoidis carbonaria, and Caiman latirostris, and 5 of Caretta caretta. The aliquots were pooled to assess concentrations of total protein, chloride, phosphorus, iron, sodium, potassium, calcium, and urea. For the tear ferning test, samples of each species were observed under a polarized light microscope at room temperature and humidity. Crystallization patterns were graded according Rolando and Masmali scales. There was more total protein and urea in owl and sea turtle tears, respectively, than in the other animals tested. Electrolyte balance was similar for all species, with higher sodium, chloride, and iron. In birds, Rolando-scale grades of tear crystallization patterns ranged from I to II, and from 0 to 2 using the Masmali scale; in reptiles, grades were II to IV (Rolando) and 2 to 4 (Masmali). Crystallization arrangements of some species had higher scores, as caimans and sea turtles, possibly due to different the tear composition. Marine and lacustrine species presented higher. The ionic balance of lacrimal fluids of birds and reptiles was similar to that in humans, with higher values of sodium and chloride. However, a similar tear composition did not influence the crystal morphology. Crystallization classification suggested that higher grades and types are due to the different microelements present in the tears of wild species.